2016
DOI: 10.1111/acer.12975
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Association Between Alcohol and HIV Virologic Failure in a Military Cohort on Antiretroviral Therapy

Abstract: Background The effects of at-risk drinking on HIV infection remain controversial. We investigated the impact of self-reported alcohol consumption on surrogate markers of HIV progression among individuals initiated on highly active antiretroviral therapy (HAART). Methods We analyzed individuals who were surveyed on alcohol use within a year of HAART initiation between 2006-14. At-risk drinking was defined as consumption of at least three or four drinks/day, or seven and 14 drinks/week among women and men, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
3
18
0
1
Order By: Relevance
“…Of the several prospective studies conducted in the prehighly active ART era (Chandiwana et al., ; Eskild and Petersen, ; Kaslow et al., ; Penkower et al., ; Tang et al., ; Veugelers et al., ; Webber et al., ), none found an association between alcohol consumption and the onset of the acquired immune deficiency syndrome (AIDS). In the highly active ART era, after controlling for ART use, 4 prospective studies found no association between heavy drinking and HIV disease progression, as measured by CD4 cell count or HIV viral load (Chander et al., ; Cook et al., ; Ghebremichael et al., ; Kowalski et al., ), and 1 identified an increased risk of virological failure associated with heavy alcohol use (Deiss et al., ). Two earlier prospective studies that separately examined HIV disease progression among those not on ART found that heavy alcohol consumption was associated with lower CD4 cell count (Samet et al., ) and shorter time to CD4 cell count <200 cells/mm 3 (Baum et al., ), but not differences in HIV viral load (Baum et al., ; Samet et al., ).…”
Section: Alcohol Use and The Hiv Treatment Cascadementioning
confidence: 99%
“…Of the several prospective studies conducted in the prehighly active ART era (Chandiwana et al., ; Eskild and Petersen, ; Kaslow et al., ; Penkower et al., ; Tang et al., ; Veugelers et al., ; Webber et al., ), none found an association between alcohol consumption and the onset of the acquired immune deficiency syndrome (AIDS). In the highly active ART era, after controlling for ART use, 4 prospective studies found no association between heavy drinking and HIV disease progression, as measured by CD4 cell count or HIV viral load (Chander et al., ; Cook et al., ; Ghebremichael et al., ; Kowalski et al., ), and 1 identified an increased risk of virological failure associated with heavy alcohol use (Deiss et al., ). Two earlier prospective studies that separately examined HIV disease progression among those not on ART found that heavy alcohol consumption was associated with lower CD4 cell count (Samet et al., ) and shorter time to CD4 cell count <200 cells/mm 3 (Baum et al., ), but not differences in HIV viral load (Baum et al., ; Samet et al., ).…”
Section: Alcohol Use and The Hiv Treatment Cascadementioning
confidence: 99%
“…13 Alcohol use is associated with HIV care including: testing 1416 and diagnosis; 17 care engagement, 18 quality, 19 and retention; 2023 receipt and use of ART; 24,25 and potentially viral suppression. 2628 Thus, alcohol use may represent a modifiable influence on HIV care continuum targets. 2928 …”
Section: Introductionmentioning
confidence: 99%
“…While a large literature has reported associations between alcohol use and HIV-relevant outcomes (Williams et al, 2016a), including HIV disease severity (Baum et al, 2010; Deiss et al, 2016; Samet et al, 2007), longitudinal studies are rare. Further longitudinal work is needed to understand which specific patterns of alcohol use increase risks and how changes in alcohol use may alter the course of HIV-related outcomes over time (Williams et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%